Management of Sport Tourism Development Based on Local Potential as a Strategy to Increase Sports Tourism Visits - Hikmat Kodrat (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of sports tourism is a potential strategy for increasing sports tourism visits while simultaneously driving local economic growth. However, various studies indicate that sports tourism development in many regions is still oriented toward organizing short-term sporting events and has not been fully integrated with local potential and sustainability principles. This study aims to examine and analyze trends in sports tourism research for the 2020–2025 period, focusing on the role of destination development management based on local potential in increasing sports tourism visits. The research method used was a systematic literature review of relevant scientific articles, using a descriptive analysis and thematic synthesis approach. The study results indicate that the success of sports tourism development is largely determined by the integration of local potential, community involvement, well-planned sports event management, and cross-sectoral synergy between the government, tourism actors, and local communities. Furthermore, the application of sustainability principles, encompassing economic, social, and environmental aspects, has proven crucial in maintaining the competitiveness and sustainability of sports tourism destinations. This study confirms that a management model for sports